LGBT’s Human Rights in the Indonesian Interior Policies - Muthmainnah, Yulianti (Yayasan Jurnal Perempuan, 2015)
Human rights which were convened by international laws and United Nations is at present universally ideal. However in implementation, this universality was contrained by interior politics, soveregnity, religious interpretation, and culture. Issues of LGBT has received wave of protests internationally and nationally though their rights are guaranteed within laws. Include LGBT issue has been debated on the national an local level. On the other hand, state has responsibility to promote, to protect, and to fulfill human rights for every single person, even people with sexual orientation and gender identity from any harms and violences. This paper will explore how human rights in Indonesia interior politics will protect LGBT groups.